ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS V SEKOLAH DASAR DI DESA SUKOLILO PATI TERHADAP PENGERJAAN SOAL BERBASIS PEMBUKTIAN - Silmi Fadhila Arida; Muhammad Faizul Ikhsan (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
Mathematical reasoning ability is one of the basic abilities that students need to have in the process of solving mathematical problems both in learning and in daily activities. This research was conducted to find out and analyze the reasoning abilities of elementary school students in working on proof-based math problems. The methodology used is quantitative based by giving question sheets to fifth grade students which are then analyzed how the results of the answers that have been answered by several students. From the questions that have been done by 10 students of class V, the results obtained with the criteria (very good) are obtained by 2 students, (good) are obtained by 3 students, (enough) are obtained by 3 students, (poor) are obtained by 2 students. Based on these results it is concluded that the reasoning ability of the class V on evidence-based questions in the village of Sukolilo Pati has quite good reasoning abilities.